1986
DOI: 10.1103/physrevlett.56.2284
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Freezing in KCN-KBr Studied by Magnetic Resonance

Abstract: The NMR line shape and spin-echo behavior of 13 C and 15 N NMR in powder samples of K(CN)o, 5 Bro,5 are reported. The line shape and spin-echo data are best explained by the molecules' developing increasingly preferred orientations as the temperature is decreased. Models in which the molecular reorientations simply slow down with decreasing temperature do not fit our data. The quadrupolar freezing is nearly complete at temperatures well above the dielectric freezing temperature. The NMR results from KCN-KBr ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…9,11,12 This anomaly has been interpreted as evidence for the formation of a quadrupolar glass state.11, 13 There is now evidence that, in these systems, dipolar (head-to-tail) and quadrupolar (orientational) freezing temperatures differ. 14,15 In order to rationalize the effect of dilution on the formation of an orientational glass state, theoretical work has invoked the coupling of the rotational degrees of freedom of the CN" anions to the random strain fields generated by the chemical disorder of the anion sublattice. 16 We have reached similar conclusions on the basis of computer simulation studies which indicated that the ground-state structure of (KBr),_x(KCN)x and related systems was determined principally by a competition between translation-rotation and strain-rotation couplings.17…”
Section: Introductionmentioning
confidence: 99%
“…9,11,12 This anomaly has been interpreted as evidence for the formation of a quadrupolar glass state.11, 13 There is now evidence that, in these systems, dipolar (head-to-tail) and quadrupolar (orientational) freezing temperatures differ. 14,15 In order to rationalize the effect of dilution on the formation of an orientational glass state, theoretical work has invoked the coupling of the rotational degrees of freedom of the CN" anions to the random strain fields generated by the chemical disorder of the anion sublattice. 16 We have reached similar conclusions on the basis of computer simulation studies which indicated that the ground-state structure of (KBr),_x(KCN)x and related systems was determined principally by a competition between translation-rotation and strain-rotation couplings.17…”
Section: Introductionmentioning
confidence: 99%
“…At all temperatures below 32 K, stimulated echoes in 5/55/40 have a decay constant longer than 2 s, a factor of lo5 longer than TZRL Thus, if the homogeneous distribution of 7, model is correct, the distribution must be exceedingly broad. At 16 K, the decay time is longest (12 s); this is the same temperature as the maximum in T2 and minimum in TI (see below): Stimulated echoes at long times also can be formed in Hz (33,38) and in KCN/KBr (21).…”
Section: Resultsmentioning
confidence: 99%
“…1 are presented I3C nrnr spectra from CO/N2/Ar (20140140) along with 15N spectra from KCN/KBr (50150) for comparison (21). In both cases the linewith is dominated by the chemical shift anisotropy of the molecule, a uniaxially symmetric tensor.…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been interpreted as evidence for the formation of a quadruplar glass state.46,110 It is generally accepted that, in these systems, dipolar (head-to-tail) and quadrupolar (orientational) freezing temperatures differ. 111,112 In one of the earliest applications of the constantpressure MD method, Impey, Klein, and Sprik investigated the cubic -*• orthorhombic transition in pure KCN. 113 In their study, the CN" charge distribution was represented by a three-site model, with charges of -0.8 e at the N site, +0.8 e in the C-N bond a distance 0.204 A from the C atom, and -e outside the C-N bond a distance 0.222 A from the C atom.…”
Section: Structural Transitionsmentioning
confidence: 99%
“…The observation of a low-temperature monoclinic phase accords well with experiment and is by itself a gratifying result, especially when we recall that the ground-state of pure KCN is orthorhombic. However, the monoclinic phase is experimentally preceded by a rhombohedral phase which forms at 112 K and whose range of existence is only about 4 K. Accordingly, a more careful study of the same site-disordered sample, this time using much smaller temperature intervals on cooling, was carried out. Results are shown in Figure 17b.…”
Section: Structural Transitionsmentioning
confidence: 99%